Avaliação das características estruturais de bolos com redução calórica - Cavalcante, Rosane Souza (2012)
The consumption of cakes with calorie reduction is growing, but has presented challenges to be overcome in the formation of its structure when the sugar or fat are replaced by sweeteners, gums, thickeners or fat substitutes. The present study was to investigate the internal characteristics of cakes with calorie reduction and viability of producing the same pattern similar to conventional cake. Initially, we defined the mixing time and mass of fat source to be used in the formulation, using as parameter the specific volume. Next, we determined the pattern of the cake formulation from a factorial experimental design of the simple type, measuring the specific volume and cell count. From this formulation, sucrose and fat were partially substituted for the production of calorie reduced cake. Replacement of sugar was made in proportion of a mixture of xanthan gum (1.5%) and sucralose (1%), while the zein was used to replace fat. In cakes with sugar lowering evaluated the specific volume (VE), the cell count (CC) of the cakes, the apparent viscosity of the mass and its thermal properties by differential scanning calorimetry (DSC). In cakes with reduced fat content, the analyzes were VE, CC and apparent viscosity. It was found that the cake with increased VE was prepared with one hydrogenated vegetable fat and one (1) minute of mixing the dough. The standard formulation was defined as having 155.88 and 28.78 shares of sugar and fat, respectively. As the sugar content decreased (10.00 to 52.17%) were reduced specific volume (1.94 to 0.7 ml / g) and cell counts (from 36.2 to 4.0 cells / cm ²) the cake and the apparent viscosity of the mass (337.56 to 631.40 cP). By reducing the fat content, there were no significant differences between the samples for VE, CC and viscosity, and viable to produce cake with reduced calorie fat replacing up to 46.86%. For the results, it was observed that replacement of sugar contributed more sharply than the replacement of fat in the formation of defects in the structure of the cake. Thermograms of the mass of standard and cakes with reduced sucrose suggested that the presence of sucralose can reduce the starch gelatinization temperature, accelerating the process and causing a compression of the structure during baking, thereby facilitating the coalescing of bubbles dispersed in mass.